Striatal and Hippocampal Atrophy in Idiopathic Parkinson’s Disease Patients without Dementia: A Morphometric Analysis - Tanner, Jared J.; McFarland, Nikolaus R.; Price, Catherine C. (Frontiers in Neurology, 2017)
BACKGROUND: Analyses of subcortical gray structure volumes in non-demented idiopathic Parkinson’s disease (PD) often but not always show volume loss of the putamen, caudate nucleus, nucleus accumbens, and hippocampus. There is building evidence that structure morphometry might be more sensitive to disease-related processes than volume. OBJECTIVE: To assess morphometric differences of subcortical structures (putamen, caudate nucleus, thalamus, globus pallidus, nucleus accumbens, amygdala) as well as the hippocampus in non-demented individuals with PD relative to age and education matched non-PD peers. METHODS: Prospective recruitment of idiopathic no-dementia PD and non-PD peers as part of a federally funded investigation. T1-weighted isovoxel metrics acquired via 3T Siemens Verio for all individuals (PD n=72 (left side onset n = 27, right side onset n = 45); non-PD n = 48). FIRST (FMRIB Software Library) applications provided volumetric and vertex analyses on group differences for structure size and morphometry. RESULTS: Group volume differences were observed only for putamen and hippocampi (PD < non-PD) with hippocampal volume significantly associating with disease duration. Group shape differences were observed for bilateral putamen, caudate nucleus, and hippocampus with greater striatal atrophy contralateral to side of motor symptom onset. Hippocampal shape differences disappeared when removing the effects of volume. CONCLUSIONS: The putamen was the primary structure to show both volume and shape differences in PD, indicating that the putamen is the predominant site of basal ganglia atrophy in early to mid-stage PD. Side of PD symptom onset associates with contralateral striatal atrophy. Left onset PD might experience more extensive striatal atrophy than right onset PD. Hippocampus morphometric results suggest possible primary atrophy of CA3/4 and dentate gyrus.